Neurosciences and education at school: from mental capital and emotional education to teaching - Rocha Bidegain, Ángela Liliana (2021)
This article seeks to investigate contemporary discourses about bodily practices from the field of neurosciences to establish their effects on teaching. In turn, some lines of analysis will be proposed around the effects on Teaching of the irruption of Neurosciences in the educational field that allow the elaboration of a theory of Physical Education that renders the substantialist determinations of neurosciences inoperable, and operates teaching / enabling new "uses of the body".